2015
DOI: 10.1080/00913847.2016.1122501
|View full text |Cite
|
Sign up to set email alerts
|

Lack of concordance amongst measurements of individual anaerobic threshold and maximal lactate steady state on a cycle ergometer

Abstract: The fixed threshold of 4 mmol/l or OBLA produces slightly different and higher results than those obtained with all the methods analyzed, including MLSS, meaning an overestimation of power in the individual anaerobic threshold. The Dickhuth-TKM, Dmax and Dickhuth-WLa methods defined a high concordance on a cycle ergometer. Dickhuth-TKM, Dmax, Dickhuth-WLa described a high concordance with the power calculated to know the MLSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
0
7
0
1
Order By: Relevance
“…However, MLSS determination is time-consuming and is usually replaced by single-session tests. Certainly, these single-session tests are differently handicapped by impaired validity, accuracy, resolution, or reliability [1,15]. Most existing single-session tests use either fixed lactate concentrations [17,21] or transition/inflection points [3,7] as determination criteria for MLSS.…”
Section: Introductionmentioning
confidence: 99%
“…However, MLSS determination is time-consuming and is usually replaced by single-session tests. Certainly, these single-session tests are differently handicapped by impaired validity, accuracy, resolution, or reliability [1,15]. Most existing single-session tests use either fixed lactate concentrations [17,21] or transition/inflection points [3,7] as determination criteria for MLSS.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous research in this area are divergent. Arratibel-Imaz et al [ 49 ] demonstrated a high agreement of D max with MLSS (MD = -2.1 W, r = 0.93) using cycling GXT3 in cyclists and triathletes. Similarly, Czuba et al [ 23 ] showed a high correlation ( r = 0.97) between WR Dmax (GXT3) and WR MLSS in well-trained female and male cyclists.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining articles contained non-media-related content covering the Triathlon Australia Selection Policy [ 55 ], physiological aspects, such as effect of caffeine [ 56 ], ventilatory threshold [ 57 ], anaerobic threshold [ 58 ], physiological attributes and training practices of elite paratriathletes [ 59 , 60 ], adaptive sports ankle prosthetics [ 61 ], and nutritional supplement use of para-athletes, which included 23 paratriathletes [ 56 ]. One article investigated organizational stressors encountered by athletes with a disability, which involved 5 paratriathletes reporting on 316 organizational stressors [ 62 ].…”
Section: Introductionmentioning
confidence: 99%